Hasil Ikutan Pertanian Sebagai Pakan Ruminansia di Jawa Tengah - H Tabrany; S Hardjosuwignjo; E B Laconi; A Daryanto (Faculty of Animal Science, Bogor Agricultural University, 2007)
The major problem faced by farmers in Central Java is the fluctuation of feed availability throughout the year, with feed surplus in the rainy season and less in the dry season. The objective of this study was to evaluate the support ability of agricultural by product as ruminant feed in Central Java. Survey method was used in this study, primary and secondary data were descriptively analyzed. The results showed that based on total population of ruminants and carrying capacity of the potential production of agricultural by product, there was an excess of support ability to 3,699,674 Animal Unit (AU) based on Dry Matter (DM); 1,419,142 AU based on Crude Protein (CP) and 1,825,567 AU based on Total Digestible Nutrients (TDN). However, based on carrying capacity of effective production of agricultural by product, there was an excess of support ability of feed only for 2,003,470 AU based on DM, 335,459 AU based on CP and 687,215 AU based on TDN. Key words: agricultural by product, ruminant, Central Java